Philosophical Transformation in Pesantren Darul Huda Ponorogo: An Ontological, Epistemological, and Axiological Review - Sulton, Ahmad; Sunandito, Virgiawan Eko (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
Pragmatic considerations and authoritarian and indoctrinative approach of traditional education system typically doesn’t allow merits of participation and constructive criticism for students, which is believed to be a cogent factor behind Darul Huda Islamic Boarding School considering to change into modern education. The study analyses how the educational at Darul Huda is changing from tradition to modern with respect to philosophy of education. The data is analyzed from a qualitative perspective with ethnographic techniques including in-depth interviews with religious leaders, teachers, students, and administrators and alumni as well as observation and documentary studies. Research results show that the transformation of the philosophy of education from a traditional education system to a modern education system can be observed from the formulation of educational goals, the influence of ontological, epistemological, and axiological foundations in educational practices at Pesantren Darul Huda. This philosophical transformation opens up opportunities for modern education, which emphasizes contextual, critical, and participatory approaches, to be implemented by Pesantren Darul Huda. So, aiming to produce learners who not only master religious knowledge but also are capable of adapting to the dynamics of social change.